Migração: da ordem jurídica internacional a suas perspectivas no Brasil - Silvestre Filho, Oscar (2016)
This study aims to compare the Brazilian human rights policies for immigrants with international human rights policies. For It had been made a literature review of international legal institutions for the protection of migrants' rights. Research work have been started from Advisory Opinions study before the Inter-American Court of Human Rights, noting the concern of nations in the commitment of respect for fundamental rights, establishing a comparison with the policies implemented by the Brazilian government and its verification in practice regarding the application of the rule in the guarantee of human rights. Also noted the importance of States to establish migration policies consistent with international legal orders regarding the rights of migrants, in order to seek a balance in the creation of a universal order, marked by match rights between national and foreign.